Disability studies and the inclusive classroom critical practices for embracing diversity in education - Baglieri, Susan; Shapiro, Arthur (New York Routledge, 2017)
Disability Studies and the Inclusive Classroom is a core textbook that integrates knowledge and practice from the fields of disability studies and special education. The second edition has been fully revised and updated throughout to include stronger connections between race, class, sexual orientation, gender, and disability to emphasize intersecting identities and experiences; stronger emphasis on curriculum and teaching rather than on attitudes toward disability; and updates to current events, cultural references, resources, research literature, laws, and policies. -- Provided by publisher.
Part I: Disability and society: what is inclusive education? -- Perspectives on disability -- Cultures of exclusion -- Moving toward cultures of inclusion -- Part II: Disability in schools: conceptualizing disability in schools -- Disabilities and initial approaches for creating inclusive environments -- Part III: Curriculum and inclusive education: approaches to student diversity: an overview -- Collaborative planning and practice -- Instructional design for inclusive education -- Designing curriculum to account for disability -- Final thoughts.
"First edition published by Routledge 2012"--Title page verso.
Includes bibliographical references and index.
Keywords: People with disabilities -- Education; Inclusive education